P26 Advance care planning in swiss nursing homes: results of a focus group study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Hecht, K; Karzig-Roduner, I; Otto, T; Krones, T; Loupatatzis, B
Abstract : Background: Until now, there has not been any official ACP program in Swiss nursing homes. We implemented an already developed and successfully tested Swiss ACP program for acute care hospitals in two Swiss nursing homes. The aim of this study was to better understand the process, chances and difficulties of the implementation steps. Methods: After having informed staff and residents, interprofessional facilitators were trained via a previously developed ACP education programme based on Respecting Patient Choices (Australia) and Beizeiten Begleiten (Germany). Six month after first implementing steps, we conducted focus group interviews with the staff and the physicians and analysed data by MaxQDA and the Krueger and Casey thamic analysis. Results: Even though the data collection was very early in implementation, our results confirm some already known facts of implementing ACP in nursing homes: The staff described an increasing sense of responsibility regarding ACP but underlined that the used forms have to be tailored to the need of the different age groups. They stressed that there must not be any pressure to undergo ACP. In addition to that, our study emphasised once more that professional palliative care is also vital for ACP programs. Conclusion: The results showed that it is not enough to only train facilitators: To be successful and sustainable, the implementing process has to include the whole healthcare system. The forms used have to be homogeneous and accessible for all involved parties. Furthermore, there is a need of public relations work to increase awareness of the subject.